Development of Educational Games Based Virtual Reality Use Millelab To learn Computational Thinking (Case Study at SMK Negeri 6 Kupang) - Mau, Anjelika Novantris; Enstein, Jhon; Neno, Khatrin J. Taku (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Development of virtual reality-based educational games in Informatics subjects, Statement and Proposition Logic material using Millealab. This type of research is R&D with quantitative data analysis techniques, using the GDLC (Game Development Life Cycle) method. The purpose of this research is to determine the process of developing virtual reality-based educational games, to find out whether there is an increase in student interest in virtual reality-based educational games and using virtual box media in Statements and Logic material.